2015
DOI: 10.3390/healthcare3020324
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Addressing the Information and Support Needs of Jewish Women at Increased Risk for or Diagnosed with Breast Cancer: The Sharsheret Experience

Abstract: Approximately 12% of women living in the United States will be diagnosed with breast cancer during their lifetimes. While all women face formidable challenges posed by the threat of living with or at increased risk for breast cancer, those of Ashkenazi Jewish descent face additional challenges owing to higher BRCA1/2 mutation prevalence in this population. Amidst calls for population-based screening for hereditary breast cancer risk, much can be learned from the experiences of Jewish women about their needs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In assessments of satisfaction, most peers and recipients of the intervention were very satisfied [ 15 , 16 , 17 , 18 ]. Qualitative analyses found that peers reported feeling valuable given the support they were able to provide, while recipients reported a reduced sense of isolation and the usefulness of hearing the experiences and advice of their peers [ 15 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In assessments of satisfaction, most peers and recipients of the intervention were very satisfied [ 15 , 16 , 17 , 18 ]. Qualitative analyses found that peers reported feeling valuable given the support they were able to provide, while recipients reported a reduced sense of isolation and the usefulness of hearing the experiences and advice of their peers [ 15 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five publications described one-day interventions: these ranged from more casual retreats to more structured information sessions to a conference with seminars, teleconferences, and webinars. Discussion topics included general information about hereditary breast and ovarian cancers, risk-reducing surgeries and surveillance, and body image and sexual health [ 16 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The internet is a common resource to obtain and deliver health information, including cancer support services. One study revealed that 59% of Americans have searched online for health information, with 25% reporting that they searched online to specifically understand a health condition [ 8 ]. In recent years, using social media (SM) groups has gained popularity, especially among those affected by chronic diseases.…”
Section: Introductionmentioning
confidence: 99%